2020
DOI: 10.3390/cells9020294
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Educated Platelets and Angiogenesis in Glioblastoma: Another Brick in the Wall for Novel Prognostic and Targetable Biomarkers, Changing the Vision from a Localized Tumor to a Systemic Pathology

Abstract: Circulating platelets (PLTs) are able to affect glioblastoma (GBM) microenvironment by supplying oncopromoter and pro-angiogenic factors.Among these mediators, sphingosine-1-phophate (S1P) has emerged as a potent bioactive lipid enhancing cell proliferation and survival. Here, we investigated the effect of "tumor education", characterizing PLTs from GBM patients in terms of activation state, protein content, and pro-angiogenic potential. PLTs from healthy donors (HD-PLTs) and GBM patients (GBM-PLTs) were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Unlike other pathologies [24,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], the molecular mechanism underlying the pathophysiology of acquired coagulopathy is still not well known, although studies have reported that a few bioumoral parameters (pH, lactates, and BE) are significantly more compromised in trauma coagulopathy patients [24,32,48]. Because ours was not a pathophysiological study, we do not know whether this correlation stems from the fact that MT results more easily in coagulopathy or whether trauma coagulopathy increases the severity of the trauma itself or whether there is a mutual influence.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other pathologies [24,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], the molecular mechanism underlying the pathophysiology of acquired coagulopathy is still not well known, although studies have reported that a few bioumoral parameters (pH, lactates, and BE) are significantly more compromised in trauma coagulopathy patients [24,32,48]. Because ours was not a pathophysiological study, we do not know whether this correlation stems from the fact that MT results more easily in coagulopathy or whether trauma coagulopathy increases the severity of the trauma itself or whether there is a mutual influence.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and management of patients pre-treated with anticoagulant agents, especially direct anticoagulant, continues to pose a major challenge despite accumulating experience and awareness [ 12 , 14 , 15 , 16 , 17 , 44 , 59 , 74 , 101 , 102 , 103 , 122 , 154 , 155 , 156 , 157 , 158 , 159 ]. Idarucizumab is indicated as an antidote for the thrombin inhibitor dabigatran (5 g intravenously (R35/1B).…”
Section: Hints For Therapymentioning
confidence: 99%
“…Blood product optimal use procedures continue to evolve, and their development should be goal directed. Despite greater awareness and experience, the identification and management of patients under the effects of anti-coagulant agents remains a major challenge [12,[14][15][16][17]59,74,[101][102][103]122,[154][155][156][157][158][159]162].…”
Section: Management Of Patients With Severe Trauma In the Edmentioning
confidence: 99%
“…Intrinsic glioma cell heterogenicity, high mitotic activity, abnormal angiogenesis, and early local recurrence are responsible for the resilience of these tumors toward standard treatments [ 9 , 10 , 11 ]. Despite the biological complexity and adaptive nature of these lethal neoplasms, recent studies have identified some molecular and epigenetic markers, such as isocitrate dehydrogenase and O6-methylguanine-DNA-methyltransferase (MGMT) gene promoter, which are useful for predicting the prognosis and planning new targeted therapeutic options [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, the detection of glioma immunogenomics, alongside immunosuppressive mechanisms within the tumor microenvironment, has prompted the development of new immunotherapies [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%